Interpretasi Qs. Al-Baqarah Ayat 256 dalam Tafsir At-Tanwir Muhammadiyah serta Implikasinya Terhadap Penguatan Toleransi Beragama di Indonesia - Aryani Ika Sari; Abdullah Mahmud; Kharis Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Religious diversity in Indonesia frequently raises challenges related to freedom of belief and interreligious relations. One Qur’anic verse often cited in this discourse is QS. Al-Baqarah (2):256, which explicitly rejects coercion in matters of faith. However, interpretations of this verse vary, and not all emphasize its relevance for contemporary plural societies. This study aims to analyze the interpretation of QS. Al-Baqarah verse 256 in Tafsir at-Tanwir and to examine its implications for strengthening religious tolerance in Indonesia. This research employs a qualitative library research method with a descriptive-analytical approach. Primary data are derived from Tafsir at-Tanwir, while secondary data include scholarly books and journal articles on Qur’anic interpretation and religious tolerance. The novelty of this study lies in its focus on Tafsir at-Tanwir as a modern Indonesian tafsir that integrates textual analysis with socio-contextual considerations of pluralism. The findings reveal that Tafsir at-Tanwir firmly positions freedom of belief as a theological and ethical principle, asserting that faith cannot be imposed and that religious diversity is part of divine will (sunnatullah). This interpretation provides a normative foundation for inclusive, dialogical, and peaceful interreligious relations. In conclusion, the interpretation of QS. Al-Baqarah 256 in Tafsir at-Tanwir contributes significantly to the discourse on religious moderation and offers a relevant framework for strengthening tolerance in Indonesia’s multicultural society.